2015
DOI: 10.1002/2014ea000084
|View full text |Cite
|
Sign up to set email alerts
|

Magnetopause inflation under radial IMF: Comparison of models

Abstract: The solar wind with the radial interplanetary magnetic field (IMF) flowing around the Earth's magnetosphere can result in significant decrease of a total pressure in the magnetosheath that was directly observed by Time History of Events and Macroscale Interactions during Substorms satellites. Observations also showed that the dayside magnetosphere enlarged and the magnetopause inflated far away from the Earth that differs from the classical hydrodynamic case. Full understanding of the magnetosphere interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
(53 reference statements)
2
21
0
Order By: Relevance
“…The thickness of the magnetosheath also decreases in response to the radial IMF conditions as a result of expanded magnetopause [ Jelínek et al ., ]. The previous results show that the magnetopause moves about 2 R E sunward in comparison with the model predictions, having a bullet‐like or globally expanded structure [ Slavin et al ., ; Dušík et al ., ; Jelínek et al ., ; Suvorova et al ., , Suvorova and Dmitriev , , , Park et al ., ]. The magnetopause also shows a local time asymmetry in its size and shape [ Huang et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the magnetosheath also decreases in response to the radial IMF conditions as a result of expanded magnetopause [ Jelínek et al ., ]. The previous results show that the magnetopause moves about 2 R E sunward in comparison with the model predictions, having a bullet‐like or globally expanded structure [ Slavin et al ., ; Dušík et al ., ; Jelínek et al ., ; Suvorova et al ., , Suvorova and Dmitriev , , , Park et al ., ]. The magnetopause also shows a local time asymmetry in its size and shape [ Huang et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed a systematic increase of observed magnetopause distances for radial IMF conditions, from ≃0.3 R E at 90° to ≃1.7 R E at 0° or 180° cone angles with respect to empirical models. Suvorova and Dmitriev [] inspected the ability of empirical magnetopause models to predict the magnetospheric expansion and found that only 4 out of 14 models, namely, Pudovkin et al [], Kuznetsov and Suvorova [], Suvorova et al [], and Lin et al [], could predict magnetopause positions for extremely low pressures and, hence, can be useful for quantitative estimation of the magnetospheric expansion under quasi‐radial IMF orientation.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of our knowledge about the magnetopause position comes from empirical models based on a large number of spacecraft crossings. Since Fairfield [], more than 15 empirical magnetopause models have been developed (14 of them mentioned in Suvorova and Dmitriev []) which define the magnetopause using different sets of observations. However, with only several exceptions [ Dmitriev and Suvorova , ; Wang et al , ; Shukhtina and Gordeev , ], all the empirical models made some a priori assumptions about the magnetopause shape.…”
Section: Introductionmentioning
confidence: 99%